Minimizing Turnover Intention with The Approach of Work Pressure and Work Stress - Rahmania; Rohilayati, Dede (Journal of Management Research and Studies, 2023)
The purpose of this research was to determine the role of work stress in mediating the impact of work pressure on turnover intention in non-medical employees at Kasih Husada Hospital. This research uses a descriptive approach with explanatory research. The variables examined in this study are work pressure, work stress, and turnover intention. Source of data comes from internal data. Data collection uses primary data and secondary data. The sample in this study amounted to 90 people. Data analysis was performed using PLS which produces more robust parameters without changing the sample from the population. The software used is SmartPLS 3.3.3. The test results show that work pressure has a positive and significant effect on work stress. Work pressure has a positive and significant effect on turnover intention. Work stress has a positive and significant effect on turnover intention. And, work stress is able to mediate the effect of work pressure on turnover intention in non-medical employees at Kasih Husada Hospital.